2021
DOI: 10.1186/s13662-021-03216-z
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical analysis of a delayed food chain model with additive Allee effect

Abstract: Dynamical analysis of a delayed tri-trophic food chain consisting of prey, an intermediate, and a top predator is investigated in this paper. The additive Allee effect is introduced in the prey population, and it is assumed that there is a time lag due to the gestation effect in the intermediate predator. The interference among the prey and the intermediate predator is according to Holling type II, while the interaction between the intermediate and top predators follows the Crowley–Martin functional response. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Future works focus on the discrete versions of these inequalities and their applications. [45][46][47]. x 1 (t)…”
Section: Discussionmentioning
confidence: 99%
“…Future works focus on the discrete versions of these inequalities and their applications. [45][46][47]. x 1 (t)…”
Section: Discussionmentioning
confidence: 99%
“…e time delay in the predator-prey model can cause complex behavior in the dynamics. For example, the authors in [3] considered gestation delay in the food chain model with Crowley-Martin functional response. ey showed that the presence of delay helps to stabilize the unstable near the interior equilibrium point to stable.…”
Section: The Delayed Modelmentioning
confidence: 99%
“…e predator-prey model is in uenced by many biological factors such as prey refuge [1], fear [2], and the Allee e ect [3,4]. In such models, the predator consumes its prey is given in the form of functional response, which is the function of its lone prey or both predator and its prey.…”
Section: Introductionmentioning
confidence: 99%
“…Weak Allee effect on the stability of a discrete-time predator-prey model was given in [43], and they observed that the system becomes stable from chaotic dynamics as the Allee parameter increases. Authors in [44] discussed a food chain model that experienced strange dynamics by varying Allee effect parameters, that is, the system state changes from stable to chaotic via period doubling as Allee effect increases. The effects of both Allee and fear parameters in predator-prey interaction model with prey-dependent functional response were considered in [29].…”
Section: Bogdanov-takens Bifurcationmentioning
confidence: 99%